Shape-Based Matching: Defect Inspection of lue Process in Vision System - Sulaiman , Marizan; Mohd Shah, Hairol Nizam; Lim , Wee Teck (2010)
his reasearch regrading the application of a vision algorithms sensor to monitor the operation of a system in order to control the concerning jobs and work pieces recognition that are to be made during system operation in real time.